Production of low methoxyl pectin using immobilized pectin methylesterase silica from acerola (Malpighia glabra L.) - de Assis, S. A.; Ferreira, B. S.; Fernandes, P.; Trevisan, H. C.; Cabral, JMS; Oliveira, OMMF (Wiley-Blackwell, 2006)
The aim of this work was to develop an efficient reactor for the production of low methoxyl pectin, using pectinmethylesterase (PME, EC 3.1.1.11) from acerola immobilized on silica. The immobilized enzyme was used in up to 50 successive bioconversion runs at 50 degrees C with an efficiency loss of less than 20%. The fixed-bed reactor (6.0 x 1.5 cm) was prepared using PME immobilized in glutaraldehyde-activated silica operated at 50 degrees C with an optimum flow rate of 10 mL h(-1). The bioconversion yield was shown to strongly depend on the nature of the enzymatic preparation. An efficiency of 44% was achieved when concentrated PME was used, compared with only 30% with purified PME, both after an 8-h run. The process described could provide the basis for the development of a commercial-scale process. (c) 2006 Society of Chemical Industry.
Keywords: pectinmethylesterase; acerola; reactor; purification; immobilization